개발도상국 고등교육을 위한 이러닝 플랫폼에 관한 연구 - 캄보디아 사례를 중심으로 - 막 새피로스; 권호열 (디지털콘텐츠학회논문지, 19(7), 2018)
본 연구는 개발도상국 고등교육을 위한 이러닝 플랫폼에 대하여 연구하였다. 먼저 ICT기술환경 등 이러닝 환경요인과 개발도상국을 위한 아세안사이버대학(ACU) 프로젝트를 소개한 후, 개발도상국 이러닝 플랫폼 사례로서 캄보디아 사례를 제시하였다. 캄보디아의 국가교육정책 및 ICT환경, 현지의 이러닝 수요 및 환경요소를 분석하였으며, 분석결과에 따른 이러닝 전략과 세부방안을 도출하고 이러닝 플랫폼 C-MOOC Net을 제안하였다. 제안된 방법을 검증하기 위하여 C-MOOC Net 시스템의 프로토타입을 공개소프트웨어 기반으로 개발하여 실제로 운영한 결과 C-MOOC 허브의 연계, 현지 언어의 지원, 선호강좌의 개인화 등록 등 요구사항을 충족함을 확인하였다. We investigated the e-learning platforms for higher education in developing countries. First, we introduced e-learning environmental factors such as ICT technology as well as ASEAN Cyber ​​University (ACU) project for developing countries. And then, we presented Cambodian case as an example of e-learning platform for developing countries. We analyzed the national education policy and ICT environment as well as the demands and obstacles of e-learning in Cambodia. We derived e-learning strategies and plans based on the analysis results, and finally proposed e-learning platform C-MOOC Net. In order to verify the proposed scheme, we developed prototype of C-MOOC Net system which is implemented based on open software. As a result, we have met the requirement of networking the C-MOOC hub, supporting localization of local language and personalization of favorite courses respectively. KCI Citation Count: 0